INTERCULTURAL COMMUNICATION OF A MULTICULTURAL FAMILY IN BURU REGENCY - Bin-Tahir, Saidna Zulfiqar; Bugis, Riki; Tasiana, Riany (Lingual Journal of Language and Culture; Vol 4 No 2 (2017)DO - 10.24843/LJLC.2017.v04.i02.p02, 2017)
This study aimed at; 1) exploring the process of intercultural communication in a multiculturalism family in Namlea; 2) investigating the functions of intercultural communication in a multiculturalism family; 3) knowing the multiculturalism family developing their intercultural competence. This research applied the qualitative research using a case study design. The informant of the research consisted of a multiculturalism family in Jikubesar of Buru Regency, Maluku. The data collection technique employed the observation, interview, field notes, and documentation. The technique of data analysis was data reduction, data display, and conclusion drawing. The results show that the adjusting and understanding others culture were the key of the success of the intercultural process in a multicultural family through some functions and strategies in developing the intercultural communication competence. The results of the study contributed to develop the communication model in the multicultural society such in the environment interaction. It also could be adapted as a strategy or model of teaching and learning a language in the multicultural classroom. Keywords: Intercultural communication, multicultural competence